STRATEGI MODAL SOSIAL DALAM PENGEMBANGAN KELEMBAGAAN BUMDES SEBAGAI RESILIENSI PEMBANGUNAN EKONOMI SOSIAL - Tiong, Piter; Sumaryo, Partono; Fatma, Nur (ADPERTISI, 2024)
Community service activities aim to provide understanding to the community related to social capital strategies in the institutional development of Bumdes as resilience to local economic development in order to build solid networks and cooperation among village community members. The implementation of community service activities uses the lecture and discussion method which is carried out in 2 stages, namely the stages of service planning activities, and the stages of implementation activities. The strategy of strengthening local economic development through social capital and Village-Owned Enterprises ( BUMDes) is implemented through community empowerment, participatory approach, social capital development, local business development, use of technology and innovation, promotion of local products, and monitoring and evaluation, which means that social capital strategies can play a role in developing BUMDes institutions. In addition, the implementation of this activity has run smoothly and community members have welcomed this activity.